2006
DOI: 10.1111/j.1574-6941.2006.00131.x
|View full text |Cite
|
Sign up to set email alerts
|

Community composition and activity of prokaryotes associated to detrital particles in two contrasting lake ecosystems

Abstract: The composition, distribution and extracellular enzyme activities of bacteria attached to small (2-50 microm in size) transparent exopolymer and Coomassie-stained proteinaceous particles (TEP and CSP) were examined in two lakes of different trophic status located in the Massif Central of France. TEP concentrations (10(4)-10(6) particle per L) were significantly higher in the more productive lake and were significantly related to chlorophyll a concentrations. The majority of TEP and CSP were colonized by bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
53
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 47 publications
6
53
1
Order By: Relevance
“…However, based on the results, it was observed that arabinosidase, fucosidase and rhamnosidase presented lower activity in the attached form than in the free-living form, and free enzymes revealed an important proportion (38-55 %) compared to the former (Table 2). Glucosidases (α-and β-) reached values comparable to other freshwater studies (Worm et al, 2001;Lemarchand et al, 2006). Working with fractionated samples Richardot et al (1999) registered the highest enzymatic activities for glucosidases (α-and β-) in the attached fraction (2-100 µm).…”
Section: Resultssupporting
confidence: 58%
“…However, based on the results, it was observed that arabinosidase, fucosidase and rhamnosidase presented lower activity in the attached form than in the free-living form, and free enzymes revealed an important proportion (38-55 %) compared to the former (Table 2). Glucosidases (α-and β-) reached values comparable to other freshwater studies (Worm et al, 2001;Lemarchand et al, 2006). Working with fractionated samples Richardot et al (1999) registered the highest enzymatic activities for glucosidases (α-and β-) in the attached fraction (2-100 µm).…”
Section: Resultssupporting
confidence: 58%
“…In lake epilimnia, the Bacteroidetes may comprise a large proportion of particle-associated bacteria (120,143) and seem to play a particularly important role in the degradation of complex biopolymers (115). In agreement with this inferred niche, several studies using PCR-based clone libraries and/or quantitative PCR (qPCR) have documented an increase in the propen- sity of the Bacteroidetes to occur during periods or at sites characterized by high external dissolved organic carbon (DOC) loading or alga-derived DOC inputs (48,49,116,237).…”
Section: Phylum Bacteroidetesmentioning
confidence: 99%
“…Members of the Betaproteobacteria are often cocultured with algae such as Cryptomonas sp. (156), are associated with the Cyanobacteria (52), and are often particle associated (120,191,227).…”
Section: Class Betaproteobacteriamentioning
confidence: 99%
“…Some studies have reported that more than half of the bacterioplankton in aquatic ecosystems can be attached to detrital particles (Simon, 1987;Riemann et al, 2000), and the abundance of those particles influences the density, biomass and production of the attached bacteria (Kepkay, 1994;Carrias et al, 2002). Both cladocerans and copepods can consume particles, including the attached bacteria (Shimeta, 1993;Lemarchand et al, 2006), and detrital particles with attached bacteria can often be more quantitatively important food for zooplankton than algae (Gons et al, 1992). Thus, such particles could be an important non-algal food source for crustaceans; all the more that according to Marzolf (1990), phytoplankton alone do not satisfy all of the nutritional requirements of zooplankton.…”
Section: Contribution Of Environmental Factors To Food Web Relationsmentioning
confidence: 99%